2017
DOI: 10.1155/2017/6510232
|View full text |Cite
|
Sign up to set email alerts
|

Genistein Exposure Interferes with Pharmacokinetics of Celecoxib in SD Male Rats by UPLC-MS/MS

Abstract: Objective To discuss the effects of genistein on the metabolism of celecoxib in vitro and in vivo. Method In vitro, the effects of genistein on the metabolism of celecoxib were studied using rat and human liver microsomes. In vivo, pharmacokinetics of celecoxib was evaluated in rats with or without genistein. Fifteen Sprague-Dawley (SD) rats were randomized into three groups: celecoxib (A group), celecoxib and 50 mg/kg genistein (B group), and celecoxib and 100 mg/kg genistein (C group). Single dose of 33.3 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…The extraction solution and pulverized cell residue were separated by centrifugation (10,000× g), and the supernatant was subjected to UPLC-MS/MS to determine intracellular CX. The UPLC-MS/MS analysis was performed according to the method reported by Zheng et al [24]. The UPLC system (Waters, Milford, MA, USA) equipped a binary solvent manager and a sample manager with a flow-through needle and a Waters XEVO TQD triple-quadrupole with an electrospray ionization source and a BEH C18 column (2.1 × 50 mm, 1.7 µm).…”
Section: In Vitro Cell Uptake Studiesmentioning
confidence: 99%
“…The extraction solution and pulverized cell residue were separated by centrifugation (10,000× g), and the supernatant was subjected to UPLC-MS/MS to determine intracellular CX. The UPLC-MS/MS analysis was performed according to the method reported by Zheng et al [24]. The UPLC system (Waters, Milford, MA, USA) equipped a binary solvent manager and a sample manager with a flow-through needle and a Waters XEVO TQD triple-quadrupole with an electrospray ionization source and a BEH C18 column (2.1 × 50 mm, 1.7 µm).…”
Section: In Vitro Cell Uptake Studiesmentioning
confidence: 99%
“…Several bioanalytical methods have been developed for the determination of ACF and CXB in rats and humans [12][13][14][15]. Herb-drug interaction studies of CXB with Ojeok-san, and Genistein have been reported [16,17]. Bioanalytical methods are available for the determination of andrographolide alone and in combination with other drugs [18,19].…”
Section: Introductionmentioning
confidence: 99%